Associations of sociodemographic and clinical factors with gastrointestinal cancer risk assessment appointment completion. Issue 4 (30th March 2020) - Ebrahimzadeh, Jessica E.; Long, Jessica M.; Wang, Louise; Nathanson, John T.; Siddique, Shazia Mehmood; Rustgi, Anil K.; Goldberg, David S.; Katona, Bryson W.
Abstract: Cancer risk assessment services are important for patient care; effective use requires appropriate provider referral, accurate scheduling processes, and completed attendance at booked appointments. Sociodemographic and clinical factors associated with gastrointestinal cancer (GIC)‐specific risk assessment appointments remain unstudied; therefore, we aimed to identify factors associated with appointment completion in a GIC risk assessment program at a tertiary academic center. Retrospective chart review was conducted on all patients scheduled for an appointment in the Gastrointestinal Cancer Risk Evaluation Program (GI‐CREP) between January 2016 and December 2017. Data collected included demographic and clinical factors. Chi‐square and Wilcoxon's rank‐sum tests compared variables among patients based on the study outcome of whether a GI‐CREP appointment was completed; marginal standardization was used to predict the standardized percentage of patients that had appointment completion. A total of 676 patients had a scheduled GI‐CREP appointment; 32 individuals were excluded due to incomplete information or scheduling error, resulting in 644 patients available for final analysis. Our study population was predominantly female (61%), White (77%), and married (64%), had private healthcare insurance (76%), and lacked a personal history of cancer (60%). Referrals internal to the healthcare system were most common (77%), with gastroenterologists as the most frequent referring provider (42%). Seventy‐five percent of scheduled individuals had appointment completion, while 25% of individuals did not. Independent predictors for an incomplete GI‐CREP appointment included Medicaid insurance (OR 2.45, 95% CI 1.21–4.28, p  = .01), self‐identified Black race (OR 1.97, 95% CI: 1.20–3.25, p  = .008), and personal history of cancer (OR 1.60, 95% CI 1.11–2.31, p  = .01). These data highlight existing disparities in GIC risk assessment appointment completion associated with race, health insurance coverage, and medical status. Further studies of these areas are necessary to ensure equitable access to important GIC risk assessment services.